2013
DOI: 10.1016/j.ijcard.2012.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell fatty acid levels improve GRACE score prediction of 2-yr mortality in patients with myocardial infarction

Abstract: Background Blood omega-3 and omega-6 fatty acid levels have been associated with reduced risk for total mortality in patients with stable coronary heart disease (CHD), but their relationships with mortality in the setting of myocardial infarction (MI) are unknown. Objective To determine the association between red blood cell (RBC) fatty acid levels measured at admission and 2-year mortality in MI patients, independent of the GRACE risk score, a traditional mode of risk stratification, Design Admission RBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 55 publications
3
24
0
4
Order By: Relevance
“…In the present study, we found non-significant associations (p>0.01) with the Omega-3 Index and its major component, DHA, but a significant 12% reduction in CVD mortality per SD increase in EPA levels, and a 25% reduction for the PUFA factor score. This finding is consistent with a previous study in post-MI patients where RBC EPA, but not DHA, levels significantly improved prediction of 2-year mortality over a composite risk algorithm 12 . On the other hand, both EPA and DHA were associated with lower CVD mortality in another study of elderly individuals in the US 10 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found non-significant associations (p>0.01) with the Omega-3 Index and its major component, DHA, but a significant 12% reduction in CVD mortality per SD increase in EPA levels, and a 25% reduction for the PUFA factor score. This finding is consistent with a previous study in post-MI patients where RBC EPA, but not DHA, levels significantly improved prediction of 2-year mortality over a composite risk algorithm 12 . On the other hand, both EPA and DHA were associated with lower CVD mortality in another study of elderly individuals in the US 10 .…”
Section: Discussionsupporting
confidence: 92%
“…Among past studies that examined the relations between PUFA biomarkers and risk for death 4, 716 (Supplemental Table 1), most were conducted in Scandinavia, Europe or Taiwan, only three have been done in the US. In addition, only two 4, 12 utilized red blood cells (RBCs), and both were performed in patients with known coronary heart disease (CHD). Hence the question remains open whether RBC PUFA levels are associated with risk for all-cause and cause-specific death in the general US population.…”
Section: Introductionmentioning
confidence: 99%
“…1,22 This particular assay method has now been widely used in a variety of studies that examined not only CVD but also depression and cognitive function. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Others that used different analytical methods have reported RBC n-3 FA associations with other conditions. For example, in a large cohort in China, RBC DHA was strongly and inversely associated with risk of multiple forms of chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The OMEGA-REMODEL trial suggested that the OM3 index may serve as a useful marker of treatment efficacy, 13 and it has also been shown that the Global Registry of Acute Coronary Events score had an improved c-statistic and correctly reclassified a significant proportion of patients by the inclusion of fatty acids. 14 We have previously argued that the inadmissibility of memory recall as scientific evidence limits the use of many nutritional studies, which may explain why the relation of OM3 in the diet to clinical events is looser than the association of measured blood levels of OM3 to clinical events. 12,15,16…”
Section: Accepted Manuscriptmentioning
confidence: 99%